2003
DOI: 10.1007/s00467-003-1281-3
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric thrombosis causing short bowel syndrome in nephrotic syndrome

Abstract: Nephrotic patients are at risk of developing venous and arterial thrombotic complications. Pulmonary embolism due to affected deep leg veins is by far the most common event. Renal or cerebral vein thromboses have been described. Thrombosis of arterial vessels is less frequent. Mesenteric infarction is a rare but severe complication in patients with nephrotic syndrome (NS). We report a 7-year-old boy with a steroid-dependent (SD) NS and a homozygous mutation of methylenetetrahydrofolate reductase, increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…54 Higher risk of venous thrombotic events (VTEs) and arterial thrombotic events (ATEs) has been demonstrated within the first 6 months of NS diagnosis in adults, 55 and in relation to administered drugs, steroid-sensitive NS had a lower risk of thromboembolism than steroid-resistant NS. 56…”
Section: Thrombosis In Nephrotic Syndromementioning
confidence: 99%
“…54 Higher risk of venous thrombotic events (VTEs) and arterial thrombotic events (ATEs) has been demonstrated within the first 6 months of NS diagnosis in adults, 55 and in relation to administered drugs, steroid-sensitive NS had a lower risk of thromboembolism than steroid-resistant NS. 56…”
Section: Thrombosis In Nephrotic Syndromementioning
confidence: 99%
“…It is also known that there is higher risk of TE in steroid-resistant NS than in steroid-sensitive NS12).…”
Section: Nephrotic Syndrome-related Complicationsmentioning
confidence: 99%
“…8,11 Although the risk of thrombotic events in children with NS might be lower, there is evidence that the implications of such events are greater in children. Ulinski et al 13 in their reports found mesenteric thrombosis which was responsible for a 240 cm small bowel necrosis of a 7-year-old boy, necessitating bowel resection. In the study of Hoyer et al 11 in which 26 children with NS were evaluated with pulmonary ventilation and perfusion studies during remission, a surprising 26.9% had evidence of pulmonary embolism.…”
Section: Discussionmentioning
confidence: 98%